Answer:
4.
![\displaystyle x = [y + 10]^2 - 10](https://img.qammunity.org/2021/formulas/mathematics/high-school/v28bqbnn0o1w0r8kb7e86z8lcgxqlesyut.png)
3.
![\displaystyle y = [x + 8]^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/mzwm4sor9y2pp1sajq9ljgvxa39i3zu18z.png)
2.
![\displaystyle y = [x + 9]^2 - 5](https://img.qammunity.org/2021/formulas/mathematics/high-school/bhrs2xdoavvhcgy382om198wxyovf3vhc3.png)
1.
![\displaystyle x = [y + 1]^2 - 4](https://img.qammunity.org/2021/formulas/mathematics/high-school/kpjpptoz8o86mhefx8dlqw3684yx5eswu9.png)
Step-by-step explanation:
To do this, you must perform the complete the square method
This formula will help us with our Vertex Equations when determining differences\sums of results in our C-values, which then get converted to finding our k-values in the Vertex Equation:
![\displaystyle x = a[y - h]^2 + k \\ y = a[x - h]^2 + k \\ \\ Standard\:Equation[s]: x = Ay^2 + By + C \\ y = Ax^2 + Bx + C \\ \\ \\ 4.\:x = [y^2 + 20y + 100] - 90 → x = [y + 10]^2 - 10\:(-10 = k; '-10' + 100 = 90) \\ 3.\:y = [x + 8]^2\:(TWO\:EIGHTS\:sum\:up\:to\:16\:AND\:multiply\:to\:64) \\ 2.\:y = [x^2 + 18x + 81] - 76 → y = [x + 9]^2 - 5\:(-5 = k; '-5' + 81 = 76) \\ 1.\:x = [y^2 + 2y + 1] - 3 → x = [y + 1]^2 - 4\:(-4 = k; '-4' + 1 = -3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ibasbi9bl74tui1maa2wq8j9ezkgc86iw6.png)
I am delighted to assist you anytime. ☺️